Higher energy and carbohydrate demand of interval training at a given average velocity on track versus treadmill - Niemeyer, M.; Gregor, T.; Weber, J.; Beneke, R. (Applied Physiology, Nutrition, and Metabolism, 2019)
We tested the hypothesis that because of acceleration and deceleration, the energy and carbohydrate demand are higher in interval training on a track than on a treadmill. Ten male subjects performed the same interval training on a treadmill and an outdoor track. A higher energy and carbohydrate demand on the track emphasizes that treadmill interval studies analyzing high numbers of short-lasting interval bouts are not transferable to interval running on a track.